Museum Collections and Online Users: Development of a Segmentation Model for the Metropolitan Museum of Art. Issue 2 (3rd July 2019) - Villaespesa, Elena
Abstract: This article presents a segmentation of users who visit The Metropolitan Museum of Art's online collection. The six segments defined in this study are professional researcher, personal interest information-seeker, student researcher, inspiration-seeker, casual browser, and visit planner. The study combines web analytics with more traditional survey methods to show how digital research tools can be incorporated into visitor studies in the emerging domain of online product evaluation. The results of this user research advance the understanding of museum website audiences, with detailed data and descriptions of each segment. The article argues that it is important for museums to create multiple kinds of online experiences to reflect the varying motivations, art background, context, and online behavior of website users. Moreover, the article provides a discussion on the implications of this user diversity for evaluating the impact and value of online museum collections. The evaluation framework needs to include metrics to measure the user experience by considering the online collection from three perspectives: as a resource for research and learning, as a source of inspiration, and as a tool for planning a visit to the museum.